Performance Evaluation of Ceiling Cooling with PCM in the Hot-Dry Climate of Yazd, Iran: An Experimental Analysis of Energy, Environmental, and Economic Impacts - Mehran Rabani; Mina Alafzadeh; Mehrdad Rabani (Buildings)
The present study investigates experimental cooling from the ceiling using phase change materials (PCMs) in Yazd, a city characterized by a hot and dry climate. A one-fourth scale model of a real room, measuring 4 m × 3 m × 3 m, was employed for the analysis. To evaluate system performance and the impact of PCM on energy consumption reduction, three configurations were considered: a simple PCM system, a PCM system with a fan (PCM-F), and a PCM system with a mini cooler (PCM-C). Additionally, to assess the influence of window configurations on ventilation, temperature, and comfort conditions within the model, three scenarios were examined: two open windows, one open window, and no windows. The economic analysis compared the two systems with the fan and mini cooler against a full mechanical cooling system without PCMs. Furthermore, CO2 emissions and environmental impacts associated with the systems were also evaluated. The results indicate that the presence of PCMs in the ceiling, due to heat absorption during phase change, leads to a temperature reduction of 5 to 10 °C in the ceiling and a 3.2 °C reduction in the average room temperature compared to the scenario without PCMs. The findings demonstrate that ceiling cooling with PCMs significantly contributes to energy consumption reduction during peak hours of cooling demand. Specifically, the PCM-F system results in a 92% reduction, and the PCM-C system leads to a 71% reduction in total cost compared to the reference mechanical cooling system. Additionally, the PCM-F system achieves approximately a 36% reduction, and the PCM-C system results in a 34% reduction in environmental impact relative to the reference full mechanical cooling system.